The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2007
DOI: 10.1063/1.2794731
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of enhancement/deterioration of boiling heat transfer using stable nanoparticle suspensions over vertical tubes

Abstract: Boiling heat transfer using nanofluids has been a subject of a few investigations in the past few years and incongruous results have been reported in literature regarding the same. Conflicting explanations for deterioration of pool boiling heat transfer coefficient at higher concentrations (4–16wt%) have been presented by various researchers. Recently, a few works have reported a significant enhancement in pool boiling heat transfer coefficient at lower concentrations (0.32–1.25wt%) and the physical reasons fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
54
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 128 publications
(59 citation statements)
references
References 13 publications
4
54
1
Order By: Relevance
“…In this study, their correlation [10] was further improved (Eq. (6)) to take into account the fact that heat transfer deterioration occurs when the ratio of surface roughness to nanoparticle size is near 1.0, otherwise heat transfer is enhanced as R a /d p is away from 1.0, as reported by Narayan et al [21] and Das et al [22]. …”
Section: Heat Flux Partitioning In Boiling Nanofluidsmentioning
confidence: 85%
See 1 more Smart Citation
“…In this study, their correlation [10] was further improved (Eq. (6)) to take into account the fact that heat transfer deterioration occurs when the ratio of surface roughness to nanoparticle size is near 1.0, otherwise heat transfer is enhanced as R a /d p is away from 1.0, as reported by Narayan et al [21] and Das et al [22]. …”
Section: Heat Flux Partitioning In Boiling Nanofluidsmentioning
confidence: 85%
“…12(a) illustrates that with the increasing nanoparticle size, the heat transfer is deteriorated at first, but then enhanced after the nanoparticle size exceeds the average surface roughness (100 nm). Narayan et al [21] and Das et al [22] suggested that when the nanoparticles size equals roughly to the surface roughness, the deposited nanoparticles could settle in the cavity and thus significantly reduce the active site density. On the contrary, when the nanoparticles are obviously larger or smaller than the surface roughness, the deposited nanoparticles could create more active sites and thus enhance the heat transfer.…”
Section: Analyses Of the Influencing Parametersmentioning
confidence: 98%
“…phenomenon can be also explained by using the surface particle interaction parameter (ψ), which is the ratio of average surface roughness (R a ) to average particle diameter (d p ) reported by Narayan et al [104]. They stated that at low nanoparticle concentrations for ψ≫1, the heat transfer coefficient increases, multiplying cavities to smaller sites [80].…”
Section: Accepted Manuscriptmentioning
confidence: 93%
“…They explored some prevailing CHF theories that showed a direct link between the CHF value and the wettability of the heater surface. Das et al [8] and Narayan et al [9] looked into the surface roughness, particle size, and nanoparticle concentration to see the role each parameter played in the nucleate boiling heat transfer (BHT). Sefiane [10] tried to explain the CHF enhancement created by the nanoparticle deposition due to structural disjoining pressure and contact angle pinning.…”
Section: Introductionmentioning
confidence: 99%